Electronic commerce - Schneider, Gary P. , 1952- (Cengage Learning, 2016)
Offers comprehensive coverage of emerging online business strategies, up-to-the-minute technologies, and the developments from the field that equips readers with a solid understanding of the dynamics of this fast-paced industry